The diachronic expansion of Pt. vossa mercê > você and Sp. vuestra merced > usted - Hummel, Martin (2019)
The widespread use of Pt. você and Sp. usted in America is a well-known fact. However, the explanation for their diachronic expansion is still a puzzling question. Given the fact that Pt. você and Sp. usted surfaced in Europe as late as the end of the 16th century, many authors wonder how these address pronouns could have spread over the whole colonial territories of Portugal and Spain, at a time when the colonization process was largely accomplished. The paper shows that this puzzling question is ill put. Pt. você and Sp. usted are reduced grammaticalized results of Late Medieval Pt. vossa mercê and Sp. vuestra merced. Both diachronic data and 20th century dialect data used for diachronic reconstruction show that an impressive bulk of reduced variants was in use already in the 16th century. The late fixing of one of these reduced forms, Pt. você / Sp. usted, is a simple matter of standardization. In this process, the colonial civil and military administration played an important role. In Portugal, the variants associated with the path vossa mercê > você were largely used in dialects, but ruled out by Lisbon’s elite. This is the reason why você is marginal in European Portuguese.